Let's lock them in: Collusion under Consumer Switching Costs - Niklas Fourberg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
I study consumer switching costs' effect on firms' price setting behavior in a 2x2 factorial design experiment with and without communication. For Bertrand duopolies the price level under consumer switching costs is lower vis-à-vis new consumers but not affected towards old consumers. Markets are overall less tacitly collusive which translates into higher incentives to collude explicitly. The results have antitrust implications especially for the focus of cartel screening.
Keywords: C7; C9; L13; L41; 330